2022
DOI: 10.3390/jcm11041080
|View full text |Cite
|
Sign up to set email alerts
|

Optic Disc Hemorrhage Is Not Associated with Global Choroidal Vessel Loss, but Is Associated with Localized Choroidal Vessel Loss in Glaucoma

Abstract: Purpose: To investigate the relationship between optic disc hemorrhage (ODH) and the geographic pattern (regional vs. global) of parapapillary choroidal vessel density (pCVD) loss within the β-parapapillary atrophy (β-PPA) in open-angle glaucoma (OAG) Methods: This retrospective cross-sectional study included 100 OAG eyes with visual field (VF) defects confined to a single hemifield (50 with and 50 without ODH, matched for age (≤10 years) and VF severity (≤1 decibel) at the same hemifield), as well as 50 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Similarly, LeTran observed a strong relationship between DH history and vascular wedge defects, with 65% of POAG eyes with both vascular wedges and DH having hemispheric concordance of these events 11 . Lee et al observed increased choroidal vessel density loss in localised regions which spatially corresponded to DH location in POAG eyes 22 . Further, Nishida et al observed in a longitudinal study that DH presence was a predictor of faster vessel density loss 23 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, LeTran observed a strong relationship between DH history and vascular wedge defects, with 65% of POAG eyes with both vascular wedges and DH having hemispheric concordance of these events 11 . Lee et al observed increased choroidal vessel density loss in localised regions which spatially corresponded to DH location in POAG eyes 22 . Further, Nishida et al observed in a longitudinal study that DH presence was a predictor of faster vessel density loss 23 .…”
Section: Discussionmentioning
confidence: 91%
“…11 Lee et al observed increased choroidal vessel density loss in localised regions which spatially corresponded to DH location in POAG eyes. 22 Further, Nishida et al observed in a longitudinal study that DH presence was a predictor of faster vessel density loss. 23 DH presence has long been established as being associated with glaucoma progression, despite this, the underlying link in pathology is still in debate.…”
Section: Discussionmentioning
confidence: 98%